Writing Educated Femininity: Race, Class, and Intellect in Early American Women's Literature. - Rambold, Sarabeth (Early American Studies, An Interdisciplinary Journal)
This article examines how late eighteenth-and early nineteenth-century white, middle-class American women authors constructed the trope of educated femininity in their literary works. It argues that these authors played a critical role in shaping cultural norms that framed women's education to enhance domestic roles within a white, patriarchal, and middle-class framework. By defining "proper" uses of women's intellect, their texts simultaneously offered a limited pathway for some marginalized women to access respectability—contingent upon assimilation—and reinforced rigid hierarchies based on race, class, and gender. Drawing on feminist literary scholarship and critical whiteness studies, the article analyzes how educated femininity functioned as a conservative ideologeme that contained women's intellectual agency within prescribed social boundaries. It highlights the tensions in these authors' works, revealing how education was both a potential tool for empowerment and a mechanism to uphold social order. Offering new readings of foundational novels and short stories written by white women between 1791 and 1853, this study demonstrates that the trope of educated femininity not only celebrated women's intellect but also sustained white middle-class normativity by linking intellectual worth to racial and class privilege.